2010
DOI: 10.1002/ijc.25704
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling reveals novel biomarkers in nonsmall cell lung cancer

Abstract: The development of reliable gene expression profiling technology is having an increasing impact on our understanding of lung cancer biology. Our study aimed to determine any correlation between the phenotypic heterogeneity and genetic diversity of lung cancer. Microarray analysis was performed on a set of 46 tumor samples and 45 paired nontumor samples of nonsmall cell lung cancer (NSCLC) samples to establish gene signatures in primary adenocarcinomas and squamous-cell carcinomas, determine differentially expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
174
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(192 citation statements)
references
References 23 publications
(29 reference statements)
7
174
1
Order By: Relevance
“…, 26 GSE18842, 27 and GSE31210 28 ) from GEO. This analysis showed that 96 pseudogenes were misregulated in GSE19188, whereas 40 were in GSE30219, 76 in GSE18842, and 54 in GSE31210 (Figure 1A; Table S2).…”
Section: Gse30219mentioning
confidence: 99%
“…, 26 GSE18842, 27 and GSE31210 28 ) from GEO. This analysis showed that 96 pseudogenes were misregulated in GSE19188, whereas 40 were in GSE30219, 76 in GSE18842, and 54 in GSE31210 (Figure 1A; Table S2).…”
Section: Gse30219mentioning
confidence: 99%
“…With regards to lung cancer, using a previously published gene expression study from our group (17), we found that genes that decrease upon miR-4423 overexpression are enriched among genes whose expression is increased in airway epithelium from patients with lung cancer (FDR q < 0.001; GSEA). We also found in three datasets (36)(37)(38) that the genes altered upon miR-4423 overexpression were significantly enriched among genes whose expression changed in the opposite direction in lung ADC and SCC relative to adjacent normal tissue (FDR q < 0.05; GSEA; SI Appendix, Fig. S21 A and B).…”
Section: Mir-4423 Inhibits Anchorage-independent Growth In Lung Cancementioning
confidence: 74%
“…All of these TBR2-negative tumors were morphologically pure SCCs and expressed high levels of KRT15 and the transcription factors SKI, p63 and SOX2 (Figures 3a and b), which are known prognostic indicators and markers of SCC. [26][27][28] In contrast, the TBR2-positive tumors were either ADCs or SCs, which had low or no expression of SKI, p63, SOX2 or KRT15 (Figure 3b). To determine whether the loss of TBR2 expression indicated that the TGF-beta signaling had a mechanistic role in the development of ADC and SCC, we used three different approaches: (1) genetic or pharmacological inactivation of TGF-beta signaling in premalignant and cancer-derived cell lines; (2) dominant interference with the formation of SMAD complexes in these cell lines; and (3) constitutive activation of the TGF-beta receptor signaling in premalignant KrasG12D p53 KO cells and tumors.…”
Section: Resultsmentioning
confidence: 99%